The randomized study of endovascular therapy with versus without intravenous tissue plasminogen activator in acute stroke with ICA and M1 occlusion (SKIP study). Issue 7 (October 2019) - Suzuki, Kentaro; Kimura, Kazumi; Takeuchi, Masataka; Morimoto, Masafumi; Kanazawa, Ryuzaburo; Kamiya, Yuki; Shigeta, Keigo; Ishii, Norihiro; Takayama, Yohei; Koguchi, Yorio; Takigawa, Tomoji; Hayakawa, Mikito; et al.
Rationale: Bridging therapy with endovascular therapy (EVT) and intravenous thrombolysis (IVT) has been reported to improve outcomes for acute stroke patients with large-vessel occlusion in the anterior circulation. While the IVT may increase the reperfusion rate, the risk of hemorrhagic complications increases. Whether EVT without IVT (direct EVT) is equally effective as bridging therapy in acute stroke remains unclear. Aim: This randomized study of endovascular therapy with versus without intravenous tissue plasminogen activator for acute stroke with ICA and M1 occlusion aims to clarify the efficacy and safety of direct EVT compared with bridging therapy. Methods and design: This is an investigator-initiated, multicenter, prospective, randomized, open-treatment, blinded-endpoint clinical trial. The target patient number is 200, comprising 100 patients receiving direct EVT and 100 receiving bridging therapy. Study outcome: The primary efficacy endpoint is a modified Rankin Scale score of 0–2 at 90 days. Safety outcome measures are any intracranial hemorrhage at 24 h. Discussion: This trial may help determine whether direct EVT should be recommended as a routine clinical strategy for ischemic stroke patients within 4.5 h from onset. Direct EVT would then become the choice of therapy in stroke centers with endovascular facilities. Trial registration: UMIN000021488.